Primary mucinuous adenocarcinoma of the ovary: a case report - Natu, N.; Chandwaskar, N.; Agrawal, Sweta; Dudani, Khushboo (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ovarian neoplasms are common tumours in females comprising 23% of all gynecologic tumours and are the most common gynecologic malignancy. Ovarian cancer is primarily a disease of postmenopausal women, the highest number of cases being concentrated in the age group from 50 to 70 years. They are the 5th leading cause of cancer related deaths in women. Primary Mucinuous cystadenocarcinoma of ovary is very rare. Our reported case was 50 years old woman which came in our OPD of Sri Aurobindo Institute of Medical Sciences with vague symptoms of lower abdominal pain and swelling. The data were collected by history-taking, clinical examination, laboratory investigations, ultrasonographic examination, CECT abdomen, CA 125, and by histo-pathological study of the excised surgical specimen. The case was reported as a rare ovarian mucinous cystadenocarcinoma. New and improved screening modalities are required for early diagnosis. And proper diagnostic criteria should be made for better prognosis.